Quality of life following Minimally Invasive Direct Coronary Artery Bypass Grafting (MIDCABG) versus Conventional Open-Heart Coronary Artery Bypass Grafting (CABG): A 3-year data from a single centre - ADLI AZAM MOHAMMAD RAZI; Muhammad 'Abid Amir; Mohd Zamrin Dimon (UiTM Press, 2021)
Introduction: In Malaysia, MIDCABG started in 3 centers developing the technique. As the technique is gaining traction in the country, this study aims to compare the quality of life following MIDCABG compared with conventional CABG in one of the centers actively developing this technique. Methods: A retrospective cohort study was performed involving 30 post CABG patients which consists of 15 MIDCABG and 15 conventional CABG from January 2015 to May 2018. 15 from 21 post-MIDCABG patients were included and selected, based on EuroSCORE II less than 5. Modified Post-Operative Quality of Recovery Scale was used to assess and compare the quality of life following respective approaches. Data were analyzed using SPSS version software and comparison using mean rank with p 0.05. Conclusion: There is no significant difference in quality of recovery following MIDCABG compared to conventional CABG. Modified PostOPQRS system can be a useful assessment tool to evaluate the impact of an intervention in relation of quality of life.